2004
DOI: 10.1007/s10265-003-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Pollen-tube growth pattern and chalazogamy in Casuarina equisetifolia (Casuarinaceae)

Abstract: For a better understanding of pollen-tube guidance in relation to pollen-pistil interaction, we investigated the mode of pollen-tube growth in pistils of Casuarina equisetifolia, a monoecious, wind-pollinated species that undergoes chalazogamous fertilization. The pistil is bicarpellate, but only one of the two carpels develops with two ovules. One of these ovules develops more than four embryo sacs. Pistils usually require more than 1 month to reach maturity after pollen grains have been deposited on the stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
7
20
0
Order By: Relevance
“…In a previous paper (Sogo et al 2004), we documented the pollen-tube growth in pistils of Casuarina equisetifolia (Casuarinaceae), and confirmed that the species undergoes chalazogamy, a mode of fertilization in which the pollen tube passes through the chalaza, instead of the micropyle (porogamy) as in the majority of angiosperms. Chalazogamy was first described by Treub (1891) in C. suberosa, and is now recognized in C. montana and C. equisetifolia (Swamy 1948;Sogo et al 2004), Allocasuarina distyla (="C. stricta") (Frye 1903), and A. nana (="C. nana") (Barlow 1958) of Casuarinaceae.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…In a previous paper (Sogo et al 2004), we documented the pollen-tube growth in pistils of Casuarina equisetifolia (Casuarinaceae), and confirmed that the species undergoes chalazogamy, a mode of fertilization in which the pollen tube passes through the chalaza, instead of the micropyle (porogamy) as in the majority of angiosperms. Chalazogamy was first described by Treub (1891) in C. suberosa, and is now recognized in C. montana and C. equisetifolia (Swamy 1948;Sogo et al 2004), Allocasuarina distyla (="C. stricta") (Frye 1903), and A. nana (="C. nana") (Barlow 1958) of Casuarinaceae.…”
supporting
confidence: 54%
“…The development of ovules is retarded compared to that of the stigma and the period between pollination and fertilization is very long. Also, as in Casuarina equisetifolia (Sogo et al 2004), the pollen-tube growth is arrested in the upper region of the style until the ovary develops to a certain extent. In the case of C. equisetifolia, the pollen tube growth proceeds through five distinct steps until fertilization after pollination (Sogo et al 2004).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The pollen tube for fertilization enters the female gametophyte directly from the chalazal, rather than the micropylar side. Nevertheless, this is not a case of chalazogamy because, in chalazogamy, the pollen tube, passing through the lateral side of the female gametophyte, extends from the chalazal to the micropylar side as in Betulaceae and Casuarinaceae (Sogo et al 2004;Sogo and Tobe 2005).…”
Section: Evolutionary Implications Of the Fertilization Mode In Cardimentioning
confidence: 95%